The effect of additional staple in the tibial fixation of anterior cruciate ligament reconstruction: a biomechanical study in sheep tibia - Oto, Onur; Bombacı, Hasan; Bozdağ, Ergun; Ertan Birsel, Sema; Bayır, Dilara; Oral, Rıdvan Mete (The European Research Journal, 2022)
Objectives: The aim of this study was to evaluate the necessity of staple use and the importance of screw diameter in the anterior cruciate ligament (ACL) reconstruction. Methods: Twenty-eight sheep hind legs were divided into four groups in terms of tibial side fixation type as 7 mm bioabsorbable screw (Group 1), 7 mm bioabsorbable screw and staple (Group 2), 8 mm screw (Group 3), and 8 mm screw and staple (Group 4). The maximum force causing insufficiency in the graft, and the fixation strength between the groups were recorded. The results were compared among the groups. Results: As a result of the statistical analysis regarding the necessity of using staple, group 2, with 7 mm screws and staple, was found to be significantly more resistant than group 1 (p = 0.018). In consequence of the biostatistics study, staple use was found not to create a statistically significant difference between group 3 in which an 8 mm bioabsorbable screw was used and group 4 (p = 0.805). In the statistical study to understand the significance of screw diameter, the samples of group 1 and group 3, in which no staple was used, were compared. It was found that group 3 samples with 8 mm screws had higher strength than those with 7 mm screws (p = 0.011). Between group 2 and group 4 in which a staple was used, despite the increase in screw diameter, the value of maximum strength had no remarkable difference statistically (p = 1.00). Conclusions: Fixation strength is higher when fixation was done with a screw 1 mm larger than tibial tunnel diameter. However, using either a screw with 1 mm wider than tibial tunnel diameter and the screw in the same diameter with the tibial tunnel and additional staple have similar fixation strength on the tibial side. Therefore, we conclude that screw width is more important in maintaining stability of the graft fixation.